Amorphous calcium phosphate-coated surfaces as a model for bone microenvironment in prostate cancer - Rebeca San Martin; Prijoyit Das; Tianchun Xue; Morgan Rose Brown; Renata Dos Reis Marques; Michael Essington; Adrian Gonzalez; Rachel Patton McCord (Heliyon)
Background: Bone metastasis remains one of the biggest challenges in the treatment of prostate cancer, and other solid tumors such as breast, lung, and colon. Modeling a complex microenvironment in-vitro such as the bone niche, requires interrogation of cell-cell interactions, specific extracellular matrix proteins, and a high calcium environment. Methods: Here, we present a fast and cost-effective system in which commercially available, non-adhesive cell culture vessels are coated with amorphous calcium phosphate (ACP) as a surrogate for bone matrix. We also present modified protocols for subculturing cells and collecting nucleic acids and protein in high-calcium samples. Results: We find that prostate epithelial cell lines show increased adhesion and proliferation when cultured in these amorphous calcium surfaces, accompanied by independence from androgen starvation. We observe gene expression changes on ACP surfaces in early adenocarcinoma cell lines which match alterations relevant to prostate cancer progression. Conclusions: Incorporating biologically relevant in-vitro systems that address the microenvironment milieu of the metastatic site is essential for accurately modeling cancer progression. In the case of bone metastasis, calcium availability, uptake, and downstream signaling are of paramount importance for the survival of the cancer cell and should be considered in the development of pre-clinical models.